Blok Saraf Perifer pada Amputasi Bawah Lutut: Telaah Sistematis - Krislee, Andre; Suhadi, Andrio; Debora, Charina Geofhany (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Background: Patients who undergo below knee amputation (BKA) surgery are often accompanied with many comorbidities so that BKA surgery with general anesthesia (GA) or spinal or epidural may not be possible. Peripheral nerve block (PNB) is an alternative to this situation. This study aims to investigate the used of PNB in BKA. Methods: We performed a detailed search of PubMed, Scopus, and Web of Science database using the following search terms and their synonyms: “peripheral nerve block”, and “below knee amputation”. Only english articles are included in this study. Data extraction and systhesis were performed according to PRIMA guidelines Results: A total 7 articles were included in this research, see table 1. For the case report and case series, five patients were undergo BKA using sciatic and femoral block combination, one patients using sciatic and lumbar plexus block combination, and five patients using sciatic and adductor canal block combination. One cohort showed that PNB had p=0.04 with adjusted OR 0.75 (0.57 – 0.98) againts GA.